BROAD-SCALE, MULTI-SYSTEM DYSREGULATION OF GENE EXPRESSION: TOWARD CLINICAL QUANTIFICATION OF AGING. (11th November 2018) - Cohen, A A; Dufour, F; Jacques, P
Abstract: Our previous work on clinical blood biomarkers established statistical distance as a proxy for dysregulation from homeostatic norms. Here, we expand this approach to gene expression data, permitting the definition of many more systems at a finer biological scale. We conducted secondary data analysis with 880 whole-blood gene expression profiles from the Rotterdam Study. Systems were defined using Gene Ontology annotations. For each system, we calculated the correlation between Mahalanobis distance and age. Among 13, 189 systems tested, 1029 showed evidence of age-related increases in dysregulation, substantially more than the 660 expected by chance. Furthermore, these systems were highly clustered, with a strong representation of systems related to immune cell function, renal function, protein localization and maintenance of proteostasis, ribosomal RNA metabolism and regulation of signaling pathways, such as the MAP kinase pathway or cell cycle phase transition pathways. These results imply the potential to develop fine-scale metrics of aging for clinical use.